BLOOD TRANSFUSION REACTION IN PATIENTS RECEIVED WHOLE BLOOD IN IRAQ-DIYALA GOVERNORATE - Mazin Razooqi Mohammed; Mustafa Gheni Taher; Fatimah Kadhim Ibrahim AL- Mahdawi (European Science Publishing, 2024)
Blood transfusion is important in the treatment of recipients in health care services as a life-saving process, even though blood transfusions can be a life-saving treatment, each transfusion carries an intrinsic hazard of reverse reactions, the current research was done to determine adverse transfusion complications after transfusion of blood units to the patient admitted to Baqubah Teaching Hospital in the Diyala - Iraq. Six thousand and four hundred eighty-three bottles of blood were dispensed form blood bank for the period from first January to the end of December 2020, data were collected from the blood monitoring department in Baqubah teaching hospital in Diyala governorate. The results were analyzed statistically by calculating the percentages of positive outcomes for each test. the data didn't show any acute serious advisers’ reaction from the blood transfusion.
Keywords: Blood, blood bank, blood group, transfusion reaction, whole blood.